A study of different treatment modalities in management of liver abscess at tertiary care center - Indrajeet, Upadhyay Prabhakar; Tripathi, Alok; Agrawal, Saurabh; Mishra , Mayank (International Surgery Journal, 2023)
Background: Of all the visceral abscesses, the liver accounts for 48%. When a purulent substance collects in the liver parenchyma as a result of bacterial, parasite, fungal, or combination infections, it is called liver abscess. It is prevalent in India, accounting for the second largest prevalence, owing to insufficient sanitation, overcrowding, and malnutrition. As the liver is a susceptible organ to producing abscesses, whereas amoebic liver abscess is the utmost frequent kind of abscess in the developing world’s tropical regions, pyogenic abscess is more prevalent in affluent nations. The aims and objectives were to study the etiology, clinical manifestation, and predisposing factors of liver abscess; to compare the conservative and surgical treatment modalities of liver abscess; and to find out the outcome of these patients. Methods: After matching inclusion and exclusion criteria, 100 clinically diagnosed liver abscess patients were enrolled for this retrospective and prospective observational study. Patients were analysed for ultrasonography whole abdomen, complete blood picture and liver function test and subjected to conservative or surgical management. Results: The study group of 100 patients consisted of 83 (83%) male and 17 (17%) female with mean age of 40 years (18-70). 89 (89%) patients managed conservatively and 11 (11%) patients underwent for surgery. Patients with conservative management were found to have significant differences between outcome. Conclusions: This study concludes that conservative management has significantly better outcomes as compared to surgical management.